Experimental study on shear behavior of HPFRC beams reinforced by hybrid pre-stressed GFRP and steel bars - Soltanzadeh, Fatemeh (2014)
The present study deals with the development of a new generation of high durable reinforced concrete (RC) beams, by combining the benefits of glass fiber reinforced polymer (GFRP), steel bar and high performance fiber reinforced concrete (HPFRC). To achieve low probability of corrosion occurrence for steel, the hybrid system of longitudinal reinforcements, composed by GFRP and steel bars, is properly disposed in order to assure a relatively thick concrete cover for the steel reinforcement. GFRP bars are placed with the minimum cover thickness in order to provide a higher internal arm and, consequently, mobilizing its capabilities efficiently. The HPFRC is designed in an attempt of being capable of replacing steel stirrups in this new structural system, since they are the most susceptible elements to corrosion. Application of prestress overcomes the detrimental effect of the relatively low modulus of elasticity of GFRP bars in terms of deflection for serviceability limit states, and introduces extra shear resistance for the beams. This paper describes an experimental program composed of four point-bending test of I-shaped cross sectional simply supported beams under monotonic load condition, and analyzes the relevant results.